2021
DOI: 10.1186/s12884-021-03941-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of coronavirus 2019 on mental health and lifestyle adaptations of pregnant women in the United Arab Emirates: a cross-sectional study

Abstract: Background In light of the pandemic, pregnant women are particularly vulnerable to increased psychological distress and in need of imperative preventive measures. This study aimed to investigate the impact of the pandemic on mental health, lifestyle adaptations, and their determinants among pregnant women in the United Arab Emirates. Methods A survey was conducted electronically between June and August 2020. Pregnant women were recruited from prena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 50 publications
(64 reference statements)
3
7
0
Order By: Relevance
“…There were 6.04% of women who maintained their current level of activity, while 2.01% increased it. A reduction of physical activity during the pandemic in pregnant women (regardless of the trimester) was also noted in studies by Hashim et al [ 58 ]—of all surveyed women, 53.6% reduced time spent on physical activity and only 13.8% increased it. In turn, Hu et al [ 59 ] showed that during the early stage of the pandemic, more nonpregnant women reduced their physical activity compared to pregnant women (50.0% vs 40.4%).…”
Section: Discussionsupporting
confidence: 70%
“…There were 6.04% of women who maintained their current level of activity, while 2.01% increased it. A reduction of physical activity during the pandemic in pregnant women (regardless of the trimester) was also noted in studies by Hashim et al [ 58 ]—of all surveyed women, 53.6% reduced time spent on physical activity and only 13.8% increased it. In turn, Hu et al [ 59 ] showed that during the early stage of the pandemic, more nonpregnant women reduced their physical activity compared to pregnant women (50.0% vs 40.4%).…”
Section: Discussionsupporting
confidence: 70%
“…The present study revealed that all pregnant women reported increased social support during the COVID-19 pandemic, which is in line with recent studies (Zhang and Ma, 2020 ; Hashim et al, 2021 ). This could be explained by the burdensome circumstances that resulted from the COVID-19 pandemic, since social support acts as a protective factor against the adverse mental health difficulties resulting from epidemics and natural disasters (King et al, 2012 ), and has been identified as an essential protection against stressful life events (Dambi et al, 2018 ).…”
Section: Discussionsupporting
confidence: 93%
“…Knowledge about how the COVID-19 pandemic affected pregnant women and new mothers is still fragmented. A systematic review of mainly Chinese studies found slightly elevated anxiety levels [ 3 ]. Similarly, we found minor changes in symptoms of depression and anxiety among Danish pregnant women in the early stage of the pandemic [ 4 ], whereas a cross-national study including data from Norway, Switzerland, Netherlands and UK found high levels of depressive symptoms and generalized anxiety in pregnant and breastfeeding women during the COVID-19 outbreak [ 5 ].…”
Section: Introductionmentioning
confidence: 99%